The women's liberation movement in Scotland - Browne, Sarah F. (Book collections on Project MUSE., 2014)
This is the first book-length account of the women's liberation movement (WLM) in Scotland. Based on documentary evidence and oral testimony from feminist activists, this book argues for the importance of looking at the movement from the grassroots perspective, as well as locating the struggle for women's liberation in the local context, shifting emphasis away from large cities like London. Not only does this book uncover the reach of the WLM but it also considers what case studies of women's liberation can tell us about the ways in which the development of the movement has been portrayed. Previous accounts have tended to equate the fragmentation of the movement with weakness and decline. This book challenges this conclusion, arguing that fragmentation led to a diffusion of feminist ideas into wider society. In the Scottish context, it also led to a lively and flourishing feminist culture where activists highlighted important issues such as abortion and violence against women. In considering the evidence from Scotland, it is shown that the history of the British movement needs to be reconsidered, presenting a vision of women's liberation as a more multi-layered, diverse and enduring movement than previously assumed. Book jacket.